Entropy, Distance and Similarity Measures under Interval Valued Intuitionistic Fuzzy Environment - Tiwari, Pratiksha; Gupta, Priti (Informatica, 2018)
This paper presents new axiomatic definitions of entropy measure using concept of probability and distance for interval valued intuitionistic fuzzy sets (IvIFSs) by considering degree of hesitancy which is consistent with the definition of entropy given by De Luca and Termini. Thereafter, we propose some entropy measures and also derived relation between distance, entropy and similarity measures for IvIFSs. Further, we checked the performance of proposed entropy and similarity measures on the basis of intuition and compared with the existing entropy and similarity measures using numerical examples. Lastly, proposed similarity measures are used to solve problems in the field of pattern recognition and medical diagnoses.